2019
DOI: 10.1590/0103-6440201902578
|View full text |Cite
|
Sign up to set email alerts
|

Bond Stability of Universal Adhesives Applied To Dentin Using Etch-And-Rinse or Self-Etch Strategies

Abstract: This study evaluated the immediate and 6-month dentin bond strength of universal adhesives used in etch-and-rinse or self-etch bonding strategies. The adhesives tested were Ambar Universal, G-Bond, Single Bond Universal, Tetric N-Bond Universal, and Ybond Universal. Gold standard adhesives (Scotchbond Multipurpose Plus and Clearfil SE Bond) were controls. Microtensile dentin bond strength (n=5 teeth), pH, and C=C conversion (n=3) were evaluated. Data were analyzed at α=0.05. All adhesives showed differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 24 publications
6
41
1
3
Order By: Relevance
“…This was confirmed by the ESEM finding as shown in fig.2D. This finding was in accordance with De Cardoso et al, 2019 (23) who demonstrated a drop in bond strength results to etched dentin after storage. Armstong et al, 2017 (24) , stated that 6 m storage for testing dentin bond strength is considered a medium to long term aging period.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was confirmed by the ESEM finding as shown in fig.2D. This finding was in accordance with De Cardoso et al, 2019 (23) who demonstrated a drop in bond strength results to etched dentin after storage. Armstong et al, 2017 (24) , stated that 6 m storage for testing dentin bond strength is considered a medium to long term aging period.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, phosphoric acid might result in formation of deep microporosities greater than the resin infiltrating potential leaving unprotected collagen fibers which are highly vulnerable to both hydrolytic and enzymatic degradation. (23,25) In addition, activation of matrix metalloproteinase enzymes (MMPs) due to dentin etching using such aggressive phosphoric acid might be another explanation for the diminished durability of microshear bond strength results. (23) Bonding to dentin using self-etch mode demonstrated stable bond strength results at 6 m storage which was also demonstrated in fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is common to find different products combined in previous research studies. This may be one of the explanations for the discrepancy in results since it has previously been determined that bond strength is highly product‐dependent and that different combinations of adhesives and composite resins may perform better than others (Cardoso, Nakanishi, Isolan, Jardim, & Moraes, 2019). The mold used in this study did not allow light to penetrate the composite from the side but only from the top.…”
Section: Discussionmentioning
confidence: 99%
“…Universal adhesives can produce moisture control without drying out, and to improve this bond, the application of a second layer of adhesive on the dentin is recommended. 3,5,[8][9] Dentin dehydration can affect the mechanical properties of the hybrid layer. 6,8 Dentin smear produced by cavity preparation also hinders the impregnation of the adhesive.…”
mentioning
confidence: 99%